Barrier Membrane In Regenerative Therapy: A Narrative Review - Muhammad Syafiq Alauddin; Nur Ayman Abdul Hayei; Muhammad Annurdin Sabarudin; Nor Haliza Mat Baharin (MDPI, 2024)
Indexed by WOS/Scopus/ERA